Legitimacy and the problem of succession to power - Nasr Mohammed Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The content of the research revolves around political legitimacy and the role of free and fair elections in strengthening the legitimacy of governments in general and consolidating the principle of peaceful transfer of power, which is the result of the democratic construction of the state. Up to the required level and in itself depends on the extent of the authority and the government to conduct free, fair and transparent elections and work with their content and to recognize the results of the elections of the results declared by the competent authority and official.